Physical-chemical and operational performance of an anaerobic baffled reactor (ABR) treating swine wastewater - 10.4025/actascitechnol.v32i4.7203 - Pereira, Erlon Lopes; Campos, Cláudio Milton Montenegro; Moterani, Fabricio (Acta Scientiarum. Technology, 2010)
Since hog raising concentrates a huge amount of swine manure in small areas, it is considered by the environmental government organizations to be one of the most potentially pollutant activities. Therefore the main objective of this research was to evaluate by operational criteria and removal efficiency, the performance of a Anaerobic Baffled Reactor (ABR), working as a biological pre-treatment of swine culture effluents. The physical-chemical analyses carried out were: total COD, BOD5, total solids (TS), fix (TFS) and volatiles (TVS), temperature, pH, total Kjeldahl nitrogen, phosphorus, total acidity and alkalinity. The ABR unit worked with an average efficiency of 65.2 and 76.2%, respectively, concerning total COD and BOD5, with a hydraulic retention time (HRT) about 15 hours. The results for volumetric organic loading rate (VOLR), organic loading rate (OLR) and hydraulic loading rate (HLR) were: 4.46 kg BOD m-3 day-1; 1.81 kg BOD5 kg TVS-1 day-1 and 1.57 m3 m-3 day-1, respectively. The average efficiency of the whole treatment system for total COD and BOD5 removal were 66.5 and 77.8%, showing an adequate performance in removing the organic matter from swine wastewater.